The Effectiveness of Virtual Reality in Improving Cognitive Function of Older Adults with Mild Cognitive Impairment: A Meta-Analysis of Randomized Controlled Trials - Jessica Dhoria Arywibowo (International Journal Labs, 2022)
Approximately 15% to 20% of the older adult population worldwide are affected by mild cognitive impairment (MCI). It is characterized by deterioration in cognitive function including memory, attention, executive function, visuospatial, or language ability. This condition leads to dementia. Therefore, cognitive training is needed to enhance cognitive function. Most cognitive training programs are conducted in conventional way. Virtual reality (VR) is a potential tool to improve cognitive function. VR is a computer-generated simulation of three- dimensional environment that gives the users a sense of presence. This meta-analysis study aimed to determine the effectiveness of VR training in improving cognitive function of older adults with MCI in comparison to conventional training. A systematic search for randomized control trials in five electronic databases yielded 18 studies with 858 participants. A random-effects analysis estimated medium effect sizes for VR training compared to conventional training in overall cognitive function outcomes (g = 0.38, 95% CI 0.04;0.71) and global cognition (g = 0.73, 95% CI 0.29;1.17). A comparison of VR and conventional training did not show significantly different effect sizes in memory (g = 0.20, 95% CI - 0.39;0.79), executive function (g = -0.26, 95% CI -0.83;0.31), and visuospatial (g = 0.45, 95% CI -0.21;1.10). These results indicate that VR training is more effective than conventional training in improving overall cognitive function and global cognition of older adults with MCI. On the other hand, VR and conventional training have equal effectiveness in improving memory, executive function, and visuospatial abilities of older adults with MCI.